Wideband distributed coherent aperture radar based on stepped frequency signal: theory and experimental results - Zeng, Tao; Yin, Pilei; Liu, Quanhua (IET radar, sonar & navigation, 2016)
As the next generation radar, although the distributed coherent aperture radar (DCAR) has been proposed and some basic works have been developed in recent years, this new radar technology has not been researched systematically. In this study, the concept and closed-loop workflow of DCAR are described in detail first. Then, the coherent parameters (CPs), which play an important role to realise full coherence in DCAR, are estimated based on orthogonal signal and coherent signal. To investigate the limits of estimation accuracy of CPs, the Cramer–Rao lower bounds are derived. The estimation values of CPs are filtered using Kalman filter to improve the estimation accuracy. In the following, the wideband full coherence technology based on stepped frequency signal is proposed to improve system robustness to time synchronisation error, which makes the DCAR technology more realisable in engineering. Furthermore, a grating lobe suppression method based on modified genetic algorithm in synthetic array pattern of DCAR is presented. Ultimately, the experiments are carried out using test system to verify the theory of wideband DCAR.